A Cross-sectional Study of Mental Health Status of Rural School Going Students in Late Adolescence Period in Southern India - R AISWARYA; KS KUMARAVEL; S RAMYA; K MANOJ; V ANUREKHA; P SAMPATHKUMAR (JCDR Research and Publications Pvt. Ltd., 2021)
Introduction: Mental health of rural adolescents is often neglected and their problems are grossly under reported. Though there are many studies available in the literature that describe the mental health status of urban adolescents, there are only a very few studies available to describe the mental health status of the rural adolescents. Aim: To assess the mental health status of adolescent boys and girls in rural schools in India. Materials and Methods: This cross-sectional descriptive study was conducted on boys and girls in late adolescence period in two rural schools. The study tool used was Strength and Difficulties Questionnaire-Youth Report 1 (SDQ-YR1) which consists of five subscales- emotional, hyperactivity, peer relationship, conduct problems and prosocial behaviours. All continuous data were described using mean and standard deviation or median and interquartile range based on the distribution. To study the association of different subscales with gender, Chi-square test or Fisher's-exact test was applied based on the expected frequency. The p-value was considered significant at 5% level of significance for all comparisons. Results: The prevalence of mental health problems as observed by the abnormal total difficulties score was 14% (n=20). The most common high risk clinically significant mental health abnormality observed was in emotional subscale which was observed in 21% of the participants. Conduct problems and hyperactivity problems were each seen in 11% of the participants. Peer problems were less often seen among the participants (6%). The abnormality in prosocial behaviour was seen in only one participant. The total difficulty score which is a sum of the emotional, conduct, hyperactivity and peer problems scale was normal in 65% of the participants, was border line in 21% and was abnormal in 14%. On the analysis of the gender variations in mental health status, a greater number of boys were found to have abnormal scores than the girls. Conclusion: This study had observed a 14% prevalence of mental health problems in rural adolescents. The mental health problems were more common in the boys than the girls. The early identification of the mental health problems by the teachers can be done by using the SDQ scale which is simple and short.